Factors predicting the effectiveness of palliative care in patients with advanced cancer - Suchira Chaiviboontham (2018)
Copyright © Cambridge University Press 2014. Objective: The purpose of this study was to assess the factors that predict the effectiveness of palliative care in patients with advanced cancer. Method: Cross-sectional data were collected from 240 patients recruited from three tertiary care hospitals in Bangkok and suburban Thailand aged 18 years or older who were willing to participate; able to speak, read, and write Thai; were not receiving aggressive cancer treatment; and had been diagnosed with advanced-stage cancer. Participants were asked to complete a Personal Information Questionnaire (PIQ), a Palliative Care Assessment Form (PCAF), and the Spiritual Well-Being Scale (SWBS). Results: The significant predictors of the effectiveness of palliative care in patients with advanced cancer were found to be spiritual well-being (p = 0.000) and palliative care strategies: a combination of pharmacological and psychosocial care, mind-body intervention, and spiritual care; physical management; and traditional medicine, herbal treatment, and diet management (p = 0.027). The likelihood of effectiveness for patients whose spiritual well-being and palliative care strategies scores increased by an average of one point increased by factors of 1.058 and 2.271, respectively. Significance of Results: These findings suggest that patients who experienced better spiritual well-being and who employed a variety of palliative care strategies also experienced enhanced effectiveness of palliative care.